The importance of the political factor in the development of public policies in Peru 2013-2016 - Benites Alvarado, Alexander (2018)
The development of public policies, defined as decisions and activities orientated to the solution of public problems requires a great number of skills and knowledge by the decision-makers and public managers. In that sense, there is an extensive literature that explains the importance of the technical skills and the ability to produce evidence of these actors. These two qualities should accompany the policy in its entire process. Nevertheless, from this perspective, we can easily lose sight of the role played by the political factor and its impact on the activities and strategies deployed by public managers. This article is based on the idea that the political factor plays a determinant role in the activities of public managers. For this reason, and due to the little delimitation of the concept, this investigation proposes to understand and analyze the political factor as 1) the coordination and 2) relationship with the political environment by public managers in the development of public policies. To do this, our analysis units are the public policies rewarded in El Concurso de Buenas Prácticas organized by La Autoridad Nacional del Servicio Civil (SERVIR), between 2013 and 2016, with the goal of proving the relevance of the political factor in the development of these practices.